2021
DOI: 10.1029/2020gl091108
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting the Permanent Loss of Lake Ice in the Northern Hemisphere Within the 21st Century

Abstract: For over 1,100 years, humans have recorded information on lake ice cover because of our dependence on ice for transportation, refrigeration, food harvest, and recreation (Knoll et al., 2019; Magnuson & Lathrop, 2014). Two of the longest ice records began for religious purposes: priests recorded and celebrated the timing of lake ice freeze in Lake Constance, Germany (875-present) and Lake Suwa, Japan (1,443-present). In stark contrast to historical patterns, Lake Constance froze for the last time in 1963 and La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 32 publications
2
22
0
Order By: Relevance
“…We found a strong relationship between observed widespread lake ice loss during the past four decades and terrestrial mean surface air temperature in the North Temperate Zone (R 2 = 0.94, p <0.05; Figures 4a, 4b and Table S1), which increased by 1.44°C from P1 to P4 (Figure 1b). This result agrees with previous studies which also found analogous relationships between temperature and lake ice based on limited in situ data sets (Sharma, Blagrave, et al, 2020). However, we detected two regions where exceptional lake conditions caused deviations from the global pattern: lakes in Region 1 (Tibetan Plateau, n = 633) which are deep (up to >100 m) and found at high altitudes (>3,300 m) (Zhang et al, 2020), and lakes in Region 2 (Yangtze Plain, n = 149) which are shallow (mostly <2 m), exhibit great interannual changes in water depth, and have suffered from extensive human activities in recent decades (Hou et al, 2020).…”
Section: Linkage To Air Temperaturesupporting
confidence: 93%
See 1 more Smart Citation
“…We found a strong relationship between observed widespread lake ice loss during the past four decades and terrestrial mean surface air temperature in the North Temperate Zone (R 2 = 0.94, p <0.05; Figures 4a, 4b and Table S1), which increased by 1.44°C from P1 to P4 (Figure 1b). This result agrees with previous studies which also found analogous relationships between temperature and lake ice based on limited in situ data sets (Sharma, Blagrave, et al, 2020). However, we detected two regions where exceptional lake conditions caused deviations from the global pattern: lakes in Region 1 (Tibetan Plateau, n = 633) which are deep (up to >100 m) and found at high altitudes (>3,300 m) (Zhang et al, 2020), and lakes in Region 2 (Yangtze Plain, n = 149) which are shallow (mostly <2 m), exhibit great interannual changes in water depth, and have suffered from extensive human activities in recent decades (Hou et al, 2020).…”
Section: Linkage To Air Temperaturesupporting
confidence: 93%
“…The phenology of lake ice (i.e., freeze/thaw dates and duration) not only influences physical conditions (such as heat storage, temperature, mixing) of underlying ecosystems (Hampton et al., 2017; O'Reilly et al., 2015; Salonen et al., 2009), but also provides important opportunities for transportation, recreation, and fishing for hundreds of millions of people worldwide (Brammer et al., 2015; Knoll et al., 2019; Prowse et al., 2011). Recently, widespread reductions in lake ice have been detected at both regional and global scales due to recent climate warming (Magnuson et al., 2000; Sharma et al., 2019), and this problem is projected to become more severe in the future due to ongoing warming trends and escalating climate extremes (Benson et al., 2012; Sharma, Blagrave, et al., 2020; Shuter et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…(2020), but we find these to become even more frequent in recent years in response to warmer air temperatures (Filazzola et al., 2020). Ice‐free years are forecasted to become more common as winter air temperatures are projected to continue to warm (Filazzola et al., 2020) and up to 5,700 northern lakes may permanently lose ice cover by the end of the century (Sharma et al., 2021). In particular, our study suggests that the ice phenology observations that were rare in the pre‐1995 climate are now much more common in the 1996–2016 period.…”
Section: Discussionmentioning
confidence: 99%
“…For example, ice fishing accounts for more than 40% of the annual fish harvest from Lake Peipsi in Estonia (Orru et al., 2014), whereas a small community in Minnesota may earn $1 million in revenue with one ice fishing tournament (Knoll et al., 2019). We highlight the importance of preserving ice cover by mitigating greenhouse gas emissions before permanently losing this invaluable environmental resource (Sharma et al., 2021).…”
Section: Discussionmentioning
confidence: 99%